Zdobycie władzy Czesława Miłosza – dzisiaj - Mokranowska, Zdzisława (Postscriptum Polonistyczne, 2020)
The theme of the article is an attempt to answer the question concerning the way in which Czesław Miłosz’s novel The Seizure of Power exists in the contemporary readers’ reception. To which extent does it nowadays fulfill (or not) the functions for which it was artistically designed half a century earlier? Is it attractive, or do the standards of reading evolved which made it oldfashioned and unable to provoke readers emotions? The article concentrates also on searching for important distinctive features for the type of novel that The Seizure of Power is or appears to be today. It can be regarded both as a novel concerning politics with a clear autobiographical suggestions and as a key novel of a certain factual value. By a contemporary (especially young) reader this first novel of the Nobel Prize Winner will be regarded as a historical prose. By literary critics and new monographers of the author of The Issa Valley it will be treated today like the caesura in Miłosz’s artistic biography – such attitude is now more visible than ever before. It marks the point from which he distances himself from political „journalism” and favors poetry, essays and criticism.